MarsTEM sensor simulations in Martian dust environment. (July 2018) - Colombatti, Giacomo; Bettanini, Carlo; Aboudan, Alessio; Debei, Stefano; Esposito, Francesca; Molfese, Cesare; Cecere, Anselmo; Merrison, John; Iversen, Jens Jacob
Abstract: A wind tunnel test campaign has been conducted prior to the landing of the Exomars2016 EDM module on the Meridiani Planum on the 19th of October 2016. Test were performed in the Mars wind tunnel facility at Aahrus University (DK) under the 2015 Europlanet Call. The facility was available for a 5 days campaign where different environmental configurations were tested and both a full scale DREAMS (Dust Characterisation, Risk Assessment, and Environment Analyser on the Martian Surface) Metmast model and a Descent Module mockup were studied. In particular the MarsTEM (Mars TEMperature sensor), the temperature sensor of the DREAMS package onboard Exomars2016, was studied for different wind velocities and directions, effect of light sources and presence of dust. The test showed that the sensor response is dependent on wind direction but only slightly on wind velocities. It also seems that the presence of the dust in the wind and the consequent dust deposit on the Metmast and the sensor itself uniforms the response for different wind velocities and directions. Light is also affecting the measurements but it is still not so clear what will be the effect on Mars due to the particular light sources used for the test.